Effects of plyometric training on muscle–tendon mechanical properties and behavior of fascicles during jumping - Keitaro Kubo (Wiley, 2021)
Abstract The purpose of this study was to investigate the effects of plyometric training on the muscle–tendon mechanical properties and behavior of fascicles during jumping in order to elucidate the mechanisms of improved jump performance due to plyometric training. Eleven subjects completed a 12‐week unilateral training program for plantar flexors. Active muscle stiffness with (100°·s−1) and without (250°·s−1) stretch reflex were calculated according to changes in muscle force and fascicle length during fast stretching after submaximal isometric contractions. Stiffness and hysteresis of tendon were measured using ultrasonography during ramp and ballistic contractions. Three kinds of unilateral jump heights using only ankle joint (no counter‐movement jump: no‐CMJ; counter‐movement jump: CMJ; drop jump: DJ) on sledge apparatus were measured. During jumping, electromyographic activities (mEMG) of plantar flexors and fascicle length of the medial gastrocnemius muscle were measured. Active muscle stiffness at 250 and 100°·s−1 and maximal tendon elongation during ballistic contraction significantly increased after training. Tendon hysteresis during ballistic contraction significantly decreased after training, whereas that during ramp contraction did not. The heights of three jump tests, the ratio of mEMG during eccentric to that during concentric phases for CMJ, and the amount of fascicle shortening and shortening velocity during eccentric phase of DJ significantly increased after training. These results suggest that an increase in CMJ height was associated with changes in the muscle–tendon mechanical properties and muscle activation strategy, whereas an increase in DJ height could be explained by changes in the muscle–tendon mechanical properties, but not muscle activation strategy.